PENDEKATAN PASTORAL KONSELING UNTUK MEMBANGUN KETAHANAN MENTAL DALAM MASA KRISIS BERDASARKAN AJARAN YESAYA 41:10 - Gloria Palinggi'; Ludia Liska, Risal, Niccolas Tamba Pakiding, Aris Tato' (ADISAM PUBLISHER, 2025)
This research aims to explore the eflectiveness of pastoral counseling approach focusing on the teachings of Isaiah 41:10 in building individual's mental resilience during crisis periods. Using a qualitative approach and case study research method, data were collected through in-depth interviews with pastoral counselors and individuals who have received pastoral counseling services. Data analysis was conducted using thematic approach to identify common patterns in respondents' experiences and perceptions regarding the development of mental resilience based on the teachings of Isaiah 41:10. The results of the study indicate that the pastoral counseling approach based on the teachings of Isaiah 41:10 has a positive impact in building individual's mental resilience during crisis periods. The principles of faith, strength, and peace contained in the verse provide a solid foundation for the pastoral counseling process. Pastoral counseling techniques such as faith-based cognitive-behavioral therapy, spiritual meditation, and practices of prayer and spiritual reflection have been proven eflective in helping individuals overcome challenges, find inner peace, and strengthen their faith. These findings contribute significantly to the field of pastoral counseling, emphasizing the importance of integrating spiritual dimension in building individual's mental resilience during crisis periods. The practical implications of this research can be used by pastoral counselors in designing and implementing counseling programs focusing on strengthening individuals' faith and mental resilience, utilizing the teachings and principles contained in Isaiah 41:10.